“Retailtainment” : standing out in the portuguese sportswear market - Martins, Rodrigo Gonçalves (2015)
The Sportswear market is a mature market where the growth is small and slow paced. In these environments, competition gets fierce and new strategies and approaches arise in pursue for successfully competitive advantage. Delivering good products at good prices is not enough anymore. People are more informed, demanding, more close to one another due to technology advances, and the companies who are audacious and courageous enough to leave their comfort zone by having consumer in mind, achieve success. Marketing shifted from masses to one-to-one, and new concepts such as Experience Marketing and “Retailtainment” start gaining bigger proportions. “Retailtainement” is not just providing entertainment at the Retail point, but much more… Is delivering experiences which are memorable, relevant, which drive brand loyalty and advocacy. Hence, considered the New Marketing Tool. The Retail, specially the sporting goods one has always been very conservative and averse to change, however it is recently changing due to the competitive aggressiveness and the appearance of these new tools. This case study places the reader, in the position of one retailer, Decathlon, which is delivering an average shop experience, in the declining competitive Portuguese Market. Decathlon main competitor and market leader, Sportzone, has recently invested in delivering a better shop experience and Decathlon is expected to fight back. To provide an authentic and detailed overview of the current Portuguese situation, an extensive research was made. The case aims then, to instigate creativity, the critical and strategical thinking, and the discussion of fresh Marketing topics, like Shop Experience.